Respiratory Physiology - Nemsadze, Ketevan (IntechOpen, 2020)
Respiratory Physiology is an open-access manual for students, postgraduates in medicine and healthcare, and clinicians in different medical specialties. Dysfunction of any component of the human respiratory system can lead to respiratory distress or failure. A comprehensive understanding of respiratory physiology can aid the practitioner in diagnosing the cause of respiratory symptoms. This book addresses aspects of respiratory physiology during exercise as well as environmental factors that affect the respiratory system. Chapters cover the most important features of human respiration, including its physiological and pathophysiological mechanisms and impacts on health and disease.